VD_FINDINFO HC / 2020 / 17 vom 21. April 2020 - VD Tribunal cantonal (2020)
LOYER INITIAL, FRAIS ACCESSOIRES, CLAUSE CONTRACTUELLE, NULLITÉ, BAIL À LOYER | 257a CO, 257b CO, 269 CO, 269a CO, 243 al. 2 let. c CPC (CH), 247 al. 2 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH)